2004
DOI: 10.1038/sj.onc.1207407
|View full text |Cite
|
Sign up to set email alerts
|

Frequent epigenetic inactivation of RASSF1A and BLU genes located within the critical 3p21.3 region in gliomas

Abstract: RASSF1A is a major tumor suppressor gene located at 3p21.3. We investigated the role of aberrant promoter region hypermethylation of RASSF1A in a large series of adult gliomas. RASSF1A was frequently methylated in both primary tumors (36/63; 57%) and tumor cell lines (7/7; 100%). Hypermethylation of RASSF1A in glioma cell lines correlated with loss of expression and treatment with a demethylating agentreactivated RASSF1A gene expression. Furthermore, reexpression of RASSF1A suppressed the growth of glioma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
88
3
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 32 publications
10
88
3
2
Order By: Relevance
“…Numerous studies in lung (Sekine et al, 2005), hepatocellular (Tischoff et al, 2005), NPC (Xiong et al, 2004), glioma (Hesson et al, 2004), and brain tumors (Horiguchi et al, 2003) suggest that chromosome 3 harbors TSGs. Positional cloning and molecular and cytogenetic approaches identified possible tumor suppressive regions mapping to 3p23 (Wang et al, 1996), 3p14.2 and 3p21.3 (Ko et al, 2001), and 3p21.1-p21.2 (Shiomi et al, 2003) in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in lung (Sekine et al, 2005), hepatocellular (Tischoff et al, 2005), NPC (Xiong et al, 2004), glioma (Hesson et al, 2004), and brain tumors (Horiguchi et al, 2003) suggest that chromosome 3 harbors TSGs. Positional cloning and molecular and cytogenetic approaches identified possible tumor suppressive regions mapping to 3p23 (Wang et al, 1996), 3p14.2 and 3p21.3 (Ko et al, 2001), and 3p21.1-p21.2 (Shiomi et al, 2003) in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of BLU/ZMYND10 is a rare event in lung cancer since missense changes were detected in only 3/61 lung tumour-cell lines (Lerman and Minna, 2000). Interestingly, however, expression of BLU/ZMYND10 is lost or downregulated in a subset of NPC, lung, neuroblastoma, kidney, breast, esophageal squamous cell carcinoma and glioma tumour-cell lines (Lerman and Minna, 2000;Agathanggelou et al, 2003b;Hesson et al, 2004;Qiu et al, 2004;Yau et al, 2006;Yi Lo et al, 2006). Promoter CpG island hypermethylation is coincident with loss of BLU/ZMYND10 expression, which can be restored following treatment with the DNA demethylating agent 5-aza-2 0 -deoxycytidine (5azaDC) (Agathanggelou et al, 2003b;Hesson et al, 2004;Qiu et al, 2004;Yau et al, 2006;Yi Lo et al, 2006).…”
Section: Rassf1mentioning
confidence: 99%
“…Interestingly, however, expression of BLU/ZMYND10 is lost or downregulated in a subset of NPC, lung, neuroblastoma, kidney, breast, esophageal squamous cell carcinoma and glioma tumour-cell lines (Lerman and Minna, 2000;Agathanggelou et al, 2003b;Hesson et al, 2004;Qiu et al, 2004;Yau et al, 2006;Yi Lo et al, 2006). Promoter CpG island hypermethylation is coincident with loss of BLU/ZMYND10 expression, which can be restored following treatment with the DNA demethylating agent 5-aza-2 0 -deoxycytidine (5azaDC) (Agathanggelou et al, 2003b;Hesson et al, 2004;Qiu et al, 2004;Yau et al, 2006;Yi Lo et al, 2006). BLU/ZMYND10 hypermethylation and downregulation has been described as a frequent event in primary tumours such as glioma (80%), cervical squamous cell carcinomas (77%), NPC (66%), neuroblastoma (41-70%) and NSCLC (19-43%) with lower frequencies observed in gall bladder carcinomas (26%), ependymomas (13.6%) and SCLC (14%) (Agathanggelou et al, 2003b;Hesson et al, 2004;Qiu et al, 2004;Abe et al, 2005;Ito et al, 2005;Marsit et al, 2005;Lai et al, 2006;Michalowski et al, 2006;Riquelme et al, 2007).…”
Section: Rassf1mentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations of human 3p frequently occur in many types of cancer, including lung carcinoma. Several studies have proven tumor-acquired promoter hypermethylation as a mechanism of inactivation of mRNA expression of some TSGs on 3p during pathogenesis of human lung cancer and several other cancers (5,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Given the fact that no genetic alterations were identified in DRR1, it was suggested that epigenetic alteration such as promoter methylation may account for the inactivity of allelic loss (3,4).…”
Section: Discussionmentioning
confidence: 99%